THE IMPACT OF LEADERSHIP STYLE AND WORK ENVIRONMENT TO EMPLOYEE’S JOB SATISFACTION WITH ORGANIZATIONAL CULTURE AS MODERATING VARIABLE AT BALAI KESEHATAN PENERBANGAN JAKARTA - Sutaryo, Kusnendar; Purwana, Dedi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The research aims to analyze the impact of leadership style and work environment to employee’s job satisfaction with organizational culture as moderating variable at balai kesehatan penerbangan Jakarta. the research used quantitative method. The data were analyzed using structural equation modeling-partial least square. 84 public services were used as samples, but 78 samples were given questionaire back. The research revealed that: a) leadership style has impact on work environment (0,549); b) leadership style influences significantly to organizational culture (0,454); c) work environment doesnot have impact on organizational culture (0,161); d) organizational culture has strong relation to job satisfaction (0,840); e) leadership style has not effect on job satisfaction (0,038); f) work environment has not influence on job satisfaction (0,037); g) throught organizational culture, leadership style hassignificant effect on job satisfaction (0,660); and h) throught organizational culture, work environment has not siginificant effect on job satisfaction (0,129).